Knowledge, attitudes, and barriers of a cohort of Iraqi dental practitioners towards the use of silver diamine fluoride in children - Al Haidar, Aseel HMJ; Bawazir, Omar A (Journal of Baghdad College of Dentistry, 2025)
Background: Silver diamine fluoride (SDF) has attracted increasing attention.since it is a conservative method that can prevent weakening of the tooth structure, postoperative pain, and the need for extensive restoration. This study aimed to investigate the knowledge, attitudes, and barriers of Iraqi dentists toward the use of SDF in children. Methods: In a cross-sectional study conducted among 406 Iraqi dentists, a Google form was used to collect data on their knowledge, attitudes and barriers to the use of SDF for children. The survey consisted of three sections: the first section collected demographic data from the participants, the second section focused on their knowledge and attitudes towards this material, and the third section identified possible barriers to its use. Statistical analysis was performed using Fisher’s exact test and the chi-square with a significance level of 5%. Results: The research revealed that 61.58% of the participants knew about this material and their knowledge was significantly related to age, sex, and speciality. Scientific lectures, discussions, and workshops were the primary sources of information (33.25%). The majority (67.9%) agreed to use this material for caries arrest, with more than 60% expressing a positive attitude toward it as a viable alternative treatment for children with behavioural issues. The primary barrier to its use was the potential for permanent black staining (77.6%). Conclusions: Although not a common practice among dentists, most of the participants agreed that using this material to treat dental caries in children is a promising method, as it requires simple instruments and does not require special training.